Ответ(ы) на вопрос:
1-ctg[latex] \alpha [/latex]/tg[latex] \alpha [/latex]-1 = (sin[latex] \alpha [/latex] - cos[latex] \alpha [/latex]) * cos[latex] \alpha [/latex] / (sin[latex] \alpha [/latex] - cos[latex] \alpha [/latex]) * sin[latex] \alpha [/latex] = cos[latex] \alpha [/latex]/sin[latex] \alpha [/latex] = ctg[latex] \alpha [/latex]
ctg[latex] \alpha [/latex] = cos[latex] \alpha [/latex]/sin[latex] \alpha [/latex]
tg[latex] \alpha [/latex] = sin[latex] \alpha [/latex]/cos[latex] \alpha [/latex]
1-ctg[latex] \alpha [/latex] = sin[latex] \alpha [/latex] - cos[latex] \alpha [/latex]/sin[latex] \alpha [/latex]
tg[latex] \alpha [/latex]-1 = sin[latex] \alpha [/latex] - cos[latex] \alpha [/latex]/cos[latex] \alpha [/latex]
Не нашли ответ?
Похожие вопросы